Зарубіжний досвід формування кадрового потенціалу - Ткаченко, А.М. (Вісник економічної науки України, 2015)
У статті розглянуто зарубіжний досвід у сфері формування кадрової політики та управління персоналом на прикладі ЄС, США та Японії. Викладено, проаналізовано та проведено порівняльну характеристику цих підходів. Зазначено, що основу концепції управління персоналом суб’єкта господарювання сьогодні складають: зростаюча роль особистості працівника, знання його мотиваційних установок, вміння їх формувати і спрямовувати відповідно до завдань, що стоять перед організацією. В статье рассмотрены зарубежный опыт в сфере формирования кадровой политики и управления персоналом на примере ЕС, США и Японии. Изложена, проанализирована и проведена сравнительная характеристика этих подходов. Обозначено, что основу концепции управления персоналом предприятия сегодня составляют все возрастающая роль личности работника, знание его мотивационных установок, умение их формировать и направлять в соответствии с задачами, стоящими перед организацией. Foreign experience of formation of human resources policy and personnel management on the example of EU, USA and Japan is considered in this article. This experience is posed and analyzed. Its comparative characteristic has been made.A growing value of worker’s individuality, knowledge of his motivational settings and the ability to shape and guide them in accordance with the organization tasks are the basis of the concept of personnel management. The situation exists in our country as well as changes in the economic and political systems carry both a great opportunities and serious threats to every individual. It brings a significant uncertainty in the life of almost every person.Ukraine has a number of problems that should be solved as soon as possible. Some of these problems are related to the sphere of enterprise human resource management. If the efficiency of personnel management will be increased, we are able to implement methods that allow us to create effective teams at enterprises. It will generate the required effect with minimum costs.